Muddy waters: An assessment of the suitability of zygocardiac ossicles for direct age estimation in the Giant mud crab Scylla serrata. (15th November 2018) - Crook, David A.; Adair, Brendan J.; Grubert, Mark A.; Saunders, Thor M.; Morrongiello, John R.; Douglas, Michael M.; King, Alison J.
Abstract: A fundamental characteristic of calcified structures commonly used for direct age estimation in animals is that new material is accreted cumulatively and preserved across ontogeny, thus allowing growth marks to be reliably observed and counted. Direct age estimation in crustaceans has been problematic due to molting of calcified structures across ontogeny; however, recent studies suggest that gastric ossicle tissue is retained through molts and can be used for age estimation. We evaluate the use of sectioned gastric ossicles for direct aging of the Giant mud crab Scylla serrata . Sectioned zygocardiac ossicles from crabs collected in northern Australia are analyzed to determine: (1) whether putative annual age estimates can be reliably reproduced; (2) if age estimates are compatible with previous information; and (3) if ossicle growth is cumulative across ontogeny. Our analyses show that readability of putative annual increments in sectioned ossicles is poor and age estimates imprecise in comparison to fish otolith studies. Age‐at‐size estimates are broadly compatible with previous mark‐recapture data from the same regions. However, analyses of ossicle growth morphology suggest that the zygocardiac ossicles are either shed or extensively reworked during ontogeny, thus casting doubt on the utility of gastric ossicles for direct age estimation in this species. We conclude that the ontogenetic growth morphology of structures used for crustacean aging needs to be carefully considered and that detailed information on the timing and frequency of increment formation—and at least some understanding of the underlying processes—is required before this method is widely adopted.